Dental caries and body mass among Peruvian schoolchildren - Christian Renzo Aquino-Canchari; Geovanny Nilton Cuya-Salvatierra (Editorial Ciencias Médicas, 2018)
Introduction: understanding the impact of metabolic disorders on health has become a global challenge in recent years. Objective: determine the relationship between body mass index and the prevalence of dental caries among Peruvian schoolchildren. Methods: adescriptive cross-sectional correlational study was conducted of 220 schoolchildren aged 6-12 years from Huando, Huancavelica, in the year 2016. The sample was randomly selected and met the inclusion and exclusion criteria. Ethical research standards were observed. Data were processed with the statistical software SPSS 21, using frequency distribution tables and the chi-squared test. Results: prevalence of dental caries was 91.82 % (CPO-D= 4.08, ceo-d= 5.81). Regarding the nutritional status, 30 children were malnourished (13.63 %) and 23 were overweight (10.45 %). The rest had a weight and height appropriate for their age, and none were obese. No statistical association was found between BMI and dental caries (p= 0.612). Conclusions: malnutrition does not predispose to the presence of carious lesions due to their multifactorial etiology, but it must be remarked that both are priority public health problems requiring the joint effort of parents and educational authorities.